2014
DOI: 10.1016/j.tsf.2013.11.049
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxygen flow and film thickness on the texture and microstructure of sputtered ceria thin films

Abstract: An in depth understanding of the influence of the deposition parameters on the texture and microstructure of sputtered ceria thin films could pave the way towards the optimization of doped ceria thin films to be applied as fuel cell related electrolytes.In this work, ceria thin films were deposited at constant current using DC reactive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…The flow control is important as other studies have shown, the structure of thin films deposited by magnetron sputtering being characterized by a function of gas flow and film thickness. [10] The machine is equipped with a box that generates vacuum. The box has a variable speed travel.…”
Section: Research On Laboratory Pilot Installations For Glass Processmentioning
confidence: 99%
“…The flow control is important as other studies have shown, the structure of thin films deposited by magnetron sputtering being characterized by a function of gas flow and film thickness. [10] The machine is equipped with a box that generates vacuum. The box has a variable speed travel.…”
Section: Research On Laboratory Pilot Installations For Glass Processmentioning
confidence: 99%
“…A Cauchy model was deemed appropriate for the ceria films, because they are fully oxidized and transparent. 15 So, a Cauchy/SiO 2 /INTR/Si model was used, which resulted in a good agreement between experimental data and fit. The film porosity was calculated from the measured refractive index using the Lorentz-Lorenz model.…”
mentioning
confidence: 96%
“…At a higher EPA or under zone II conditions, the thin films have a [111] fiber texture. 15 Target erosion will alter the angular distribution of the negative ions, but in this paper, the possible change of the energy flux and deposition rate in relation to the texture of the deposited CeO 2 thin films is also studied. In this way, the momentum and energy transfer can be separately investigated.…”
mentioning
confidence: 99%
See 2 more Smart Citations